A Two-Way Mendelian Randomization Analysis on the Link between Thyroid Activity Function and Coronary Atherosclerosis - Le-tai Li; Jia-jie Leng; Yu-xiang Luo; Rong-jia Liu; Zhuo-xuan Song; Meng Ye; Zhen-han Li; Zhen-rui Cao; Ying-jiu Jiang; Hong-tao Tie (Reviews in Cardiovascular Medicine)
Introduction: Coronary atherosclerosis serves as the primary pathological etiology underlying coronary artery disease (CAD). Thyroid hormones show potential as risk factors, aside from the main standard modifiable cardiovascular risk factors (SMuRFs). This research seeks to elucidate the link between thyroid activity and coronary atherosclerosis. Methods: Single nucleotide polymorphisms (SNPs) linked to hypothyroidism (N = 213,990), Graves’ disease (GD) (N = 190,034), other hyperthyroidism types (N = 190,799), thyroid-stimulating hormone (TSH) (N = 271,040), free thyroxine (FT4) (N = 119,120), and coronary atherosclerosis (N = 360,950) were retrieved from the IEU OpenGWAS, Finngen R9, and ThyroidOmics Consortium databases. Following the application of strict criteria to eliminate linkage disequilibrium, palindromic sequences, and heterozygous alleles, a bidirectional Mendelian Randomization (MR) analysis was conducted between the thyroid gland and coronary atherosclerosis using inverse variance weighting (IVW), weighted median (WM), and MR-Egger techniques. For sensitivity analysis, Cochran’s Q test, leave-one-out method, and MR-Egger regression analysis were employed. Results: The forward MR analysis indicates that genetic predispositions such as hypothyroidism (OR = 1.07; 95% CI 1.01–1.12; IVW-p = 0.021), Graves’ disease (OR = 1.04; 95% CI 1.01–1.07; IVW-p = 0.002), and other forms of hyperthyroidism (OR = 1.05; 95% CI 1.01–1.10; IVW-p = 0.021) elevate the likelihood of developing coronary atherosclerosis. Additionally, no discernible evidence of a causality between FT4 or TSH, and coronary atherosclerosis (IVW-p > 0.05) was found. Coronary atherosclerosis is not related to increased risk of five thyroid function phenotypes in reverse MR analysis. The sensitivity analysis provided relatively reliable evidence to reinforce the validity of our findings. Conclusions: Our findings are an investigation of the causality between thyroid function and coronary atherosclerosis. This study pinpointed potential heart disease risks linked to coronary atherosclerosis and offered additional understanding for defining SMuRFs in CAD.